1999
DOI: 10.1016/s0167-7012(98)00110-9
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of anti-peptide monoclonal antibodies with specificity for staphylococcal enterotoxins A and B

Abstract: A synthetic peptide containing selected epitopes from staphylococcal enterotoxin A (SEA) and enterotoxin B (SEB) was used to produce monoclonal antibodies (Mabs) to respective enterotoxins in a single fusion procedure. The peptide inhibited the reaction of polyclonal anti-SEA or anti-SEB antisera with their homologous enterotoxin, thus showing that the chosen epitopes are part of the antibody-inducing enterotoxin sequences. Two Mabs, Mab-A and Mab-B, reacted with both the peptide and with either SEA or SEB. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The identification of B-cell epitopes is rather important to immunotherapeutic and immunodetection applications because an epitope as the minimal immune unit is strong enough to elicit a potent humoral immune response without harmful side effects to the human body [30] . The most reliable methods for the identification of an epitope are monoclonal antibodies, X-ray crystallography and NMR techniques [26] , [31] [33] . To date, only five linear B cell epitopes of SEB have been identified by these methods, among which the truncated SEB mutant A was used to confirm SEB 252-261 as an SEB epitope [25] ; the anti-peptide monoclonal antibodies were used to reveal SEB 96-103 as an SEB epitope [27] ; the anti-TSST-1 monoclonal antibodies were used to reveal SEB 110-119 as a cross epitope of SEB and TSST-1 [25] ; and SEB 28-41 and SEB 35-40 were identified as SEB epitopes using the commercial anti-SEB monoclonal antibody ab53981 by a phage display approach [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The identification of B-cell epitopes is rather important to immunotherapeutic and immunodetection applications because an epitope as the minimal immune unit is strong enough to elicit a potent humoral immune response without harmful side effects to the human body [30] . The most reliable methods for the identification of an epitope are monoclonal antibodies, X-ray crystallography and NMR techniques [26] , [31] [33] . To date, only five linear B cell epitopes of SEB have been identified by these methods, among which the truncated SEB mutant A was used to confirm SEB 252-261 as an SEB epitope [25] ; the anti-peptide monoclonal antibodies were used to reveal SEB 96-103 as an SEB epitope [27] ; the anti-TSST-1 monoclonal antibodies were used to reveal SEB 110-119 as a cross epitope of SEB and TSST-1 [25] ; and SEB 28-41 and SEB 35-40 were identified as SEB epitopes using the commercial anti-SEB monoclonal antibody ab53981 by a phage display approach [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Epitope mapping of crucial antigens has been a useful exercise that has been done using multiple methods, including monoclonal antibodies, X-ray crystallography and Nuclear magnetic resonance techniques [ 33 36 ]. For example, a peptide was identified from PfRH5 by virus-like particle (VLP) approach and a mAb to the peptide completely inhibited parasite invasion in vitro [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the directions is convenient serological tests based on epitopes. As early as the last century, experiments have shown that ELISA methods for quantitative detection of toxins have been developed by selecting epitopes of S. aureus enterotoxins to synthesize peptides that can be used to produce mAbs [ 62 ]. Besides, it was found that the pentasacyl bridge of peptidoglycan of S. aureus has high antigenic specificity.…”
Section: Applications In Diagnosismentioning
confidence: 99%